La Lectura Crítica del Diario como Estímulo a la Reflexión de los Párvulos - Infante S., José Miguel (Re-presentaciones: Periodismo, comunicación y sociedad, 2008)
The present article is the result of research to describe the educational appro- priation for the stimulation of the development judgment moral in the children from 3 to 6 years of the nursery school by means of the use of the newspaper, in pedagogic half-full activities. The result of research was achieved to recognize new uses of the newspaper in the nursery school, from the informative point of view, because preferably it uses like waste. Also it was possible to check the values of the newspaper in education, the importance of the educators' s mediating role and the possibilities presents in the gradual stimulation of the child critical judgment development, pursue by the news publishes in the newspaper. It's pertinent remember that this mass communication essentially it's directed to the adults' world.
Keywords: Critical Reading; Development of the Moral Judgment